268 A phase 1 study of retifanlimab (INCMGA00012), a PD-1 inhibitor, in patients with advanced solid tumors: preliminary results in recurrent MSI-high or dMMR endometrial cancer (POD1UM-101). (10th December 2020) - Berton-Rigaud, Dominique; Vergote, Ignace; Pautier, Patricia; Kryzhanivska, Anna; Angelergues, Antoine; Kornacki, Deanna; Dudzisz-Sledz, Monika; Tian, Chuan; Bourayou, Nawel; Selle, Frederic
Abstract : Background: Management of patients with recurrent endometrial cancer after failure of platinum therapy remains an important clinical challenge. Tumors characterized by abnormalities in DNA repair are associated with high numbers of neoantigens, making immunotherapy a promising approach. Retifanlimab (INCMGA00012) is an investigational humanized immunoglobulin G4 monoclonal antibody against PD-1. In the dose escalation and tumor expansion portions of the POD1UM-101 phase 1 study, retifanlimab monotherapy demonstrated acceptable tolerability and durable clinical activity in multiple advanced tumor types, including pretreated endometrial cancer. Here we present interim clinical activity and safety data from a preplanned futility assessment in patients with microsatellite instability-high (MSI-H) recurrent endometrial cancer. Methods: Patients eligible for this cohort had histologically proven, unresectable recurrent endometrial cancer that was MSI-H or deficient mismatch repair (dMMR) based on local testing (either by PCR or IHC), ECOG performance status (PS) ≤1, disease progression during or following ≤5 prior systemic treatments, measurable disease per RECIST v1.1, and no prior treatment with immune checkpoint inhibitors. The primary endpoint is safety (using CTCAE v4.03 grading). Confirmed best overall response rate and duration of response were evaluated by RECIST v1.1 (investigator's assessment). Retifanlimab 500 mg Q4W was administered up to 2 years. Results: As of April 7, 2020, 44 patients who received at least 1 dose of retifanlimab were assessed for safety, including 24 patients who were fully assessable for the planned futility analysis. Median age was 63 (49–86) years, 45.5% had an ECOG PS of 1, and 97.7% had adenocarcinoma (1 had missing histology data at cut-off). Of the 44 patients treated, all but 1 were pretreated with at least 1 prior platinum-based chemotherapy, 72.7% were treated with radiotherapy, and 90.9% underwent surgery. Median drug exposure was 1.9 (0.03–11.1) months. Eight patients (18.2%) experienced Grade (G) 3/4 AEs regardless of causality with anemia being the leading event (n=3, 6.8%). Two patients (4.5%) had immune-related AEs (n=1 each: dry mouth [G3] and myositis [G3]); both patients discontinued study treatment because of the event. No treatment-related deaths occurred. Confirmed responses (7 PR, 1 CR) per RECIST v1.1 were observed, supporting study continuation. Median duration of response was not reached, as no confirmed responders had disease progression or died at time of this analysis. Conclusions: Retifanlimab was generally well tolerated with preliminary evidence of encouraging antitumor activity in MSI-H pretreated advanced endometrial cancer. Enrollment is ongoing. Acknowledgements: This study is sponsored by Incyte Corporation (Wilmington, DE). Trial Registration: NCT03059823, EudraCT 2017-000865-63 Ethics Approval: The study was approved by institutional review boards or independent ethics committees of participating institutions. Consent: n/a